Paper Strength Development with Beating and Polyamideamine-epichlorohydrin (PAE) - Maria Ulfa; Bambang Setiaji; Wega Trisunaryanti; Triyono Triyono (Indonesian Journal of Physics and Nuclear Applications, 2016)
Thecharacter of coir handsheets prepared with beating and addition of polyamideamine-epichlorohydrin (PAE) was investigated. Pulp coir from soda-anthraquinone pulping was used as raw material for manufacture of coir handsheets. Physical and mechanical properties obtained with different beating level and PAE dosage were measured. The addition of PAE 10% w/w and beating on pulp stock of 3000 rev increased grammage and density at 1.9 and 15.8%, respectively. Instead it decreased thickness by 15.8%. Addition PAE dosage of 10% w/w at 10000 rev improved the density, but decreased the porosity and Cobb60 at 5.8; 10.2; and 19 %, respectively. The highest   dry and wet tensile were obtained at 20 % w/w of PAE. Combination of  beating and addition of PAE on pulp stock formed wet-strength handsheets with range between 28.0 to 34.2%.